A qualitative investigation on the influence of social media on single individuals’ expectations of romantic relationships - Sun, Pei Li (Nanyang Technological University, 2024)
Social media platforms such as TikTok and Instagram have become increasingly popular and contain a network of shared content which potentially influences users’ expectations. Hence, when users encounter relationship content, they may be influenced to follow social scripts describing behaviours within a relationship. It has been widely confirmed that the media, which includes TV shows and movies, portrays relationships as the key to happiness, and impacts people to view romantic love in an idealised manner. However, past research has yet to explore how current social media content has influenced people’s perceptions of love. Thus, this study aimed to investigate how current social media content on relationships influences single individuals’ expectations of romantic relationships. A constructivist approach was used, and semi-structured interviews were conducted with eight participants. Data was analysed using thematic analysis within grounded theory, using Sternberg’s Triangular Theory of Love as a reference model. The findings of this study revealed social media’s tendency to promote polarised views among users, and that users combine social media content with their personal experiences and views to derive insights, whether consciously or not. This eventually leads to reinforced or newly learnt ideas on what they desire in a relationship, which influences their desire for a relationship and manifests in their future behaviours when navigating relationships. Therefore, implications of this model include exploring single individuals’ approaches to contemporary relationships and their use of social media to gain new perspectives on dating and romance.